ANALISIS INDUSTRI GORDEN DI PASAR WISATA PASAR BAWAH KOTA PEKANBARU MELALUI PENDEKATAN STRUCTURE, CONDUCT, PERFORMANCE - Hasibuan, Yustika Laura; Harahap, Azwar; ', Harlen (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research aims to determine the structure, behavior and performance in the Travel Market Market Down Pekanbaru. The data obtained from the primary data used by the author by means of questionnaires with census method due to the spread of the business units are relatively concentrated in these markets. In this study the authors use the approach Structure-Conduct-Performance (SCP). in the calculation of seeking market structure done in 2 ways ie by the method of measuring the concentration ratio of 4 major companies and the calculation method using the Herfindahl index-Hirscman (IHH). With this method the concentration ratio of 4 large companies (CR4) found a yield of 0.325%. Which means that the value of CR4 in industrial curtains in Travel Market Market Down Pekanbaru is the type that is kind of perfect competition monopolistic market. From the results of research using CLR calculation (Capital To Labour) industrial curtains in Travel Market Market Down Pekanbaru City found a figure of 106.32%, which means the curtain at this location industry is capital intensive industry group. Then the benefits PCM is not affected by the market share is correct. So we can conclude that the benefits do not come from the market share. And an undertaking which has a market share does not guarantee to be able to have a greater advantage anyway.Keyword: Structure, Conduct, Performance